Modelling Islamic Banking Efficiency by Decomposing using D.E.A. Bootstrapping Analysis - Mustafa, Atta ul; Zahoor, Zunaira (Islamic Banking and Finance Review, 2022)
This research determined the efficiency of Islamic banks operating in the Pakistan region. This study will also help understand which bank performs poorly and best according to our time period. The study used the bootstrap D.E.A. approach for the time period of 2008-2018. The bootstrap D.E.A. approach removes the biases error by repeatedly replicating the data-generating process and using the actual measurement for each sample made. The study found out that the mean value of efficiencies for Islamic banks of Pakistan is greater than 1, so banks are running optimally. However, BankIslami Pakistan needs to increase its efficiency because it works way below its optimal level. This study adds excellent value to the literature by opening a new direction for the study of Islamic banks in Pakistan. Only a few studies have been done on this topic, which is not mainly related to Pakistan.